Effect of coal gangue grading characteristics on cemented paste backfill rheology - Hao Li; Hongjiang Wang; Longjian Bai (Case Studies in Construction Materials, 2024)
In the field of coal mine backfilling, the method of grading the coal gangue and the effect it has on the rheological properties of the cemented paste backfill (CPB) are still to be fully understood. In this study, the CPB is composed of coal gangue as the coarse aggregate, fly ash and cement as the fine aggregate. The properties of the coal gangue were characterised in terms of porosity and friction angle, and the comprehensive influence of different coal gangue grading, volume fraction and CPB mixture ratios on the rheological properties of the CPB was investigated. The experimental results indicate that both large and small coal gangue particle sizes can increase the porosity and friction angle. Compared with single grade and gap grade, coal gangue with continuous grade (G32) has a lower porosity of 42.1 %, a friction angle of 43.8 °, a yield stress of 7.6Nm and a viscosity of 6.5Nm, a higher slump of 221 mm, and a water film thickness of 1.68 μm. The yield stress has been identified as the primary factor influencing the slump of CPB. The yield stress and viscosity of the CPB are negatively correlated with the particle size, mortar ratio, and slump, and positively correlated with the volume fraction of coal gangue. In addition, the significant impact of various factors on the rheological parameters of the CPB is ranked as porosity> mortar ratio >volume fraction>friction angle. The relationship between yield stress, viscosity and water film thickness (WFT) is a power function, and the established WFT model can conveniently and quickly predict the rheological parameters of the CPB.